Cost-effectiveness of ocriplasmin for the treatment of vitreomacular traction and macular hole. Issue 1 (1st January 2016) - Bennison, Craig; Stephens, Stephanie; Lescrauwaet, Benedicte; Van Hout, Ben; Jackson, Timothy L.
Abstract : Background: If left untreated, vitreomacular traction (VMT) will infrequently improve through spontaneous resolution of vitreomacular adhesion (VMA), and patients remain at risk of further deterioration in vision. The mainstay of treatment for VMT is vitrectomy, an invasive procedure that carries the risk of rare but serious complications and further vision loss. As such, a 'watch and wait' approach is often adopted before this surgical intervention is performed. Ocriplasmin (microplasmin) is a potential alternative treatment for patients with symptomatic VMA/VMT that may remove the requirement for vitrectomy. Objective: The purpose of this study was to evaluate the cost-effectiveness of ocriplasmin for the treatment of VMT in comparison to standard of care. Study design: A cohort-based computer simulation model was developed, capturing three mutually exclusive subgroups: 1) VMT without epiretinal membrane (ERM) or full thickness macular hole (FTMH), 2) VMT with ERM but no FTMH, and 3) VMT with FTMH. Transition probabilities between health states, utilities, and resource utilisation were estimated based on clinical trial results, the literature, and expert opinion. The cost per quality-adjusted life year (QALY) gained was estimated over a lifetime, using UK unit costs and utilities associated with visual acuity, adverse events, metamorphopsia, and surgical interventions. Setting: Analyses were conducted from a UK payer perspective. Population: Transition probabilities for the model were primarily estimated from patient-level data from the combined Phase 3 MIVI-TRUST trials in patients with symptomatic VMA/VMT, including when associated with a FTMH ≤400 µm. Intervention: Ocriplasmin (microplasmin) is a one-time intravitreal injection designed specifically to release the abnormal traction between the macula and the vitreous and thereby treat VMT, as well as macular hole with persistent vitreous attachment. Main outcome measure: The main outcome measure of the economic evaluation was cost per QALY. Results: In all subgroups, ocriplasmin management generated more QALYs: 1) VMT without ERM or FTMH (0.105, (0.036, 0.191)); 2) VMT with ERM but no FTMH (0.041, (0.011, 0.131)); and 3) VMT with FTMH (0.053, (−0.002, 0.113)). The initial treatment costs were partially offset by later savings and net costs were estimated at £1, 901 (£1, 325, £2, 474), £2, 491 (£1, 067, £2, 511), and £1, 912 (£1, 233, £2, 506), respectively. Costs per QALY were estimated at £18, 056 (£8, 241, £64, 874), £61, 059 (£8, 269, £168, 664), and £36, 250 (−£144, 788, £290, 338), respectively. Short-term efficacy parameters were found to be key drivers of results. Conclusion: Ocriplasmin is most cost-effective in VMT patients without either ERM or FTMH.